Protective and curative effects of Phuong Dong Dai Trang tablets on an experimental model of irritable bowel syndrome - Tung, Tran Thanh; Van Anh, Pham Thi; Duong, Dau Thuy (Tạp chí Nghiên cứu Y học, 2024)
Phuong Dong Dai Trang tablet is a mixture of medicinal herbs including Hedychium coronarium, Coix lacryma-jobi, Dioscorea persimilis, Cynara Scolymus L., Paeonia lactiflora, and Glochidion eriocarpum. This study was carried out to evaluate the protective and curative effects of Phuong Dong Dai Trang tablets on mustard oil-induced irritable bowel syndrome model in mice. Swiss mice were divided into six groups that were given orally 0.9% sodium chloride (group 1 - 3), Duspatalin (mebeverine) 80 mg/kg b.w./day (group 4), Phuong Dong Dai Trang tablets 1080 mg/kg b.w./day (group 5) and Phuong Dong Dai Trang tablets 3240 mg/kg/b.w./day (group 6). Mice of group 3 - 6 were induced diarrhea-predominant irritable bowel syndrome by mustard oil colonic administration before or after oral treatment. The research indices included the intestinal motility measured by charcoal meal test, colon macroscopic and microscopic scores. Our findings showed that Phuong Dong Dai Trang tablets at 3240 mg/kg b.w./day reduced the intestinal motility and the stool score significantly in mice. Phuong Dong Dai Trang tablets at 1080 mg/kg b.w./day improved the stool score and tended to decrease the intestinal motility in mice.